Diagnostic value of plasma RNF180 gene methylation for gastric cancer: A systematic review and meta-analysis - Wang, Tongxin; Zhang, Yating; Wang, Jianrong; Li, Yumin (Frontiers in Oncology, 2023)
Objective A systematic evaluation of the diagnostic value of Ring finger protein 180 (RNF180) gene methylation as a novel tumor marker for gastric cancer (GC) is required to improve the early diagnosis of gastric cancer patients. Methods Computer searches of PubMed, Web of Science, Embase, The Cochrane Library, CNKI, CBM, WanFang Data, National Research Register, Cclinical Controlled Trials, Opengreyand VIP databases were conducted from the database's inception to September 1, 2022. Two researchers independently screened the literature, extracted information, and assessed the risk of bias in studies that were included. The meta-analysis was carried out using RevMan 5.3 and Stata 16.0 software. Results A total of 9 studies with a total of 1531 subjects were included. A random-effects meta-analysis revealed that the combined sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) of plasma RNF180 gene methylation for the diagnosis of GC were: 0.54 [95% CI (0.45, 0.62)], 0.80 [95% CI (0.72, 0.87)], 2.73 [95% CI (2.09, 3.57)], 0.58 [95% CI (0.51, 0.65)], 4.74 [95% CI (3.59, 6.62)], respectively. Conclusion The detection of RNF180 gene methylation in plasma has a high diagnostic value for GC and is expected to be a potential biomarker for the diagnosis of gastric cancer, according to current evidence.